A Flexible Test for Present Bias and Time Preferences using Land-Lease Contracts - Pieter A. Gautier; Aico van Vuuren (Tinbergen Institute, 2011)
When agents have present bias, they discount more between now and thenext period than between period t (> 1) and t + 1. How fast the future discount rate (evaluated today) decays is an empirical question. Weshow that the discount function can be non-parametrically identified withcontracts that specify payments that take place at various points in timein the future and which are traded and priced in a competitive market.We use a unique land lease-contract data set for Amsterdam, which hasthe above properties, to test for present bias in a flexible way. We findno evidence for present bias in this market. Even though we allow for ageneral-hyperbolic specification (which has exponential discounting as aspecial case), our estimates converge to an exponential discount functionwith a corresponding discount rate (in our baseline specification) of 8 %.
urn:NBN:nl:ui:31-1871/38533
Keywords: C52; D03; D12; 330; present bias; hyperbolic discounting; discount rate; hedonic estimation; Zeitpräferenz; Abzinsung; Bodennutzung; Immobilien-Leasing; Amsterdam